2011
DOI: 10.1016/j.mee.2011.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Transfer printing approach to all-carbon nanoelectronics

Abstract: Transfer printing methods are used to pattern and assemble monolithic carbon nanotube (CNT) thin-film transistors on large-area transparent, flexible substrates. Airbrushed CNT thin-films with sheet resistance 1k  square -1 at 80% transparency were used as electrodes, and high quality chemical vapor deposition (CVD)-grown CNT networks were used as the semiconductor component. Transfer printing was used to pre-pattern and assemble thin film transistors on polyethylene terephthalate (PET) substrates which incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…All-CNT TFTs with a split bottom-gate structure can be fabricated by the layer-by-layer transfer technique. [202,203] Zou et al reported such all-CNT TFTs and inverter circuits, as shown in Figure 10. [203] The two kinds of CNT network were fabricated by controlling the density of the network through CVD and then successively transferring them to the flexible substrate to construct the devices.…”
Section: Carbon Nanotubes As Electrodesmentioning
confidence: 99%
“…All-CNT TFTs with a split bottom-gate structure can be fabricated by the layer-by-layer transfer technique. [202,203] Zou et al reported such all-CNT TFTs and inverter circuits, as shown in Figure 10. [203] The two kinds of CNT network were fabricated by controlling the density of the network through CVD and then successively transferring them to the flexible substrate to construct the devices.…”
Section: Carbon Nanotubes As Electrodesmentioning
confidence: 99%
“…5h). 243,244 Furthermore, CNT-based transparent conductors have application in photovoltaics as will be described below.…”
mentioning
confidence: 99%
“…Estas formas irregulares le confieren a las nanoplaquetas efectos electrostáticos importantes que propician su aglomeración, tal como se puede observar en la Figura 5 (parte izquierda), los cuales podrían influenciar de forma significativa el transporte electrónico en ellas y en dispositivos electrónicos del tipo de los micropuentes (Sangwan, et al, 2011).…”
Section: Resultados Y Discusiónunclassified